PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, RISIKO TINGKAT BUNGA TERHADAP PROFITABILITAS DENGAN STRUKTUR KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL - Eriyanto, Desiana Bella; Bambang Sudiyatno (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to evaluate the effect of credit risk, liquidity risk, interest rate risk on profitability with managerial ownership structure and firm size as control variables in conventional banking companies listed on the IDX in 2016 – 2020. The data used are secondary data in the form of financial statements and financial statements. annual report for 2016-2020. Technical analysis of the data using multiple linear regression analysis, sampling was carried out by purposive sampling with a total sample of 26 companies from a total population of 40 companies, so the number of observations was 130. The test results show that credit risk has a negative and significant effect on profitability, liquidity risk has a positive and insignificant effect on profitability, interest rate risk has a positive and significant effect on profitability, managerial ownership structure has a negative and insignificant effect on profitability, and firm size has a positive and significant effect on profitability. significant to profitability.